Pemberdayaan Masyarakat Penyandang Disabilitas Dalam Meningkatkan Kesejahteraan Ekonomi Perspektif Maqasyid Syariah - Dienillah, Izzah (LAN TABUR : Jurnal Ekonomi Syariah, 2025)
People with disabilities are often faced with problems of poverty, difficulty in getting work, and the fulfillment of basic rights which have an impact on welfare problems. This study aims to understand the stategy for improving the welfare of people with disabilities through empowerment, and the rationale for empowering the welfare of people with disabilities at the Department of Social Affairs, Women’s Empowerment, Child Protection and Family Planning (Dinsos P3AKAB) of Bondowoso Regency in terms of maqashid sharia. This research uses a qualitative approacj with a case study research type, using primary data obtained from interviews and observations and supported by secondary data through related literature. Data analysis in this study was carried out in three steps: data reduction, data presentation, and conclusion. Meanwhile, checking the validity of the data uses data triangulation techniques. The study results of the study show that empowering of people with disabilities by the Social Service P3AKAB of Bondowoso Regency through skills training, capital assistance, and market access assistance is a strategic step that can improve the welfare of people with disabilities. This approach is in line with the maqashid sharia which includes the protection of religion, soul, mind, property, and descendants